2001
DOI: 10.4319/lo.2001.46.7.1642
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation of the balance between plankton photosynthesis and respiration in the eastern Atlantic Ocean

Abstract: A knowledge of the balance between plankton gross primary production (GPP) and community respiration (CR) in the open ocean is vital to the accurate determination of the global carbon cycle, yet the paucity of open ocean measurements severely limits our understanding. This study measured GPP, net community production, dark CR, and size-fractionated primary production in the upper 200 m of a 12,100 km latitudinal (32ЊS-48ЊN) transect in the Eastern Atlantic Ocean during May and June 1998. This comprehensive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
108
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 89 publications
(127 citation statements)
references
References 55 publications
18
108
1
Order By: Relevance
“…Furthermore, the northern subtropical gyre is on average 50-100% more productive, when expressed per unit chla, than the southern subtropical gyre. These trends of P max ðP max chla Þ are consistently observed in other independent investigations based on O 2 evolution (Serret et al, 2001;Robinson et al, 2002, Gonza´lez et al, 2002 and C assimilation (Serret et al, 2001;Teira et al, 2005;Pe´rez et al, 2005) measurements.…”
Section: Energetic Coupling In Subtropical and Tropical Atlantic Provsupporting
confidence: 75%
See 2 more Smart Citations
“…Furthermore, the northern subtropical gyre is on average 50-100% more productive, when expressed per unit chla, than the southern subtropical gyre. These trends of P max ðP max chla Þ are consistently observed in other independent investigations based on O 2 evolution (Serret et al, 2001;Robinson et al, 2002, Gonza´lez et al, 2002 and C assimilation (Serret et al, 2001;Teira et al, 2005;Pe´rez et al, 2005) measurements.…”
Section: Energetic Coupling In Subtropical and Tropical Atlantic Provsupporting
confidence: 75%
“…Fluxes of these elements between phytoplankton and their surrounding environment indicate the net community metabolism and thus the trophic structure of the food web and significance of carbon sequestration (Karl et al, 1998;Serret et al, 2001;Gonza´lez et al, 2002). Furthermore, the light-response of these productivity measurements describe the physiological status of photoautrophic communities that then can be applied to models investigating environmental change Maran˜o´n and Holligan, 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our net community production rates integrated over the euphotic layer (NCP int : 132 6 48 to 1328 6 95 mmol O 2 m 22 d 21 ) are among the highest reported rates for the North Atlantic. Previous studies near the western end of our study area reported net autotrophy with NCP int in the region of 50-100 mmol O 2 m 22 d 21 (Serret et al 2001;Gist et al 2009). The Lagrangian nature of our study allowed us to track changes in the biogeochemistry of the upwelled filaments P-1 and P-3.…”
Section: Discussionmentioning
confidence: 94%
“…Gross production and R incubations-Additional incubations were carried out on deck for the determination of GPP, net primary production, and R (Serret et al 2001;Gist et al 2009). Samples were collected predawn from six depths in 10 liter acid-cleaned carboys (wrapped in black plastic bags to minimize light exposure).…”
Section: Methodsmentioning
confidence: 99%